2022
DOI: 10.1136/bmjopen-2021-057444
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned nursing home admission among discharged polymedicated older inpatients: a single-centre, registry-based study in Switzerland

Abstract: ObjectiveTo investigate patient characteristics and the available health and drug data associated with unplanned nursing home admission following an acute hospital admission or readmission.DesignA population-based hospital registry study.SettingA public hospital in southern Switzerland (Valais Hospital).ParticipantsWe explored a population-based longitudinal dataset of 14 705 hospital admissions from 2015 to 2018.Outcome measuresSociodemographic, health and drug data, and their interactions predicting the risk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…Although we found no statistically significant associations between the prescription of analgesics at discharge and hospital readmission,28 discharge-day pain scores have previously been associated with 30-day hospital readmissions 61. Indeed, our logistic regression analysis revealed that older adults with analgesic prescriptions had a higher probability of unplanned nursing home admission (adjusted for age, sex, number of comorbidities and functional status) 29. Four participants and their informal caregivers described inadequate pain management during our qualitative phase, which might be explained by poor discharge planning and older adults’ complaints of not feeling sufficiently listened to or involved in medication-related decisions.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Although we found no statistically significant associations between the prescription of analgesics at discharge and hospital readmission,28 discharge-day pain scores have previously been associated with 30-day hospital readmissions 61. Indeed, our logistic regression analysis revealed that older adults with analgesic prescriptions had a higher probability of unplanned nursing home admission (adjusted for age, sex, number of comorbidities and functional status) 29. Four participants and their informal caregivers described inadequate pain management during our qualitative phase, which might be explained by poor discharge planning and older adults’ complaints of not feeling sufficiently listened to or involved in medication-related decisions.…”
Section: Discussioncontrasting
confidence: 76%
“…The mean hospital length of stay was 8.6 days (SD=7.6). The mean number of drugs prescribed at hospital discharge was 9.1 (SD=3.3), with means of 10.9 (SD=3.9) drugs for patients discharged to a nursing home versus 8.9 (SD=3.2) for those discharged home 29…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Without preventative measures, MRPs can lead to physical and cognitive decline, exacerbated chronic medical conditions, rehospitalisations, avoidable health costs [9][10][11], and, sometimes, unplanned institutionalisation [12]. Nurses can play a crucial preventative role in ensuring safe medication management for polymedicated home-dwelling older adults [13,14].…”
Section: Introductionmentioning
confidence: 99%